RECYCLING OF CONSTRUCTION TIMBER WASTE TO ENERGY : A CASE STUDY IN SWCORP - Yee Lin, Ng; Abu Hassan, Zahiruddin Fitri; Abdul Halim, Imaduddin (Journal of Surveying, Construction and Property, 2021)
In recent years, there are increasing environmental issue due to the construction waste especially in Malaysia. Timber waste has covered two thirds percentage of the construction waste. Hence, potential on construction timber waste recycling to energy specifically in Malaysia under the states with solid waste managed by Solid Waste and Public Cleansing Corporation (SWCorp) is being studied. The research objectives are to investigate the improvement factors and current practices by the timber waste contractors in Malaysia. The study was conducted using a mixed method research approach to SWCorp officer, timber waste contractors and timber recycling center representatives to discover in depth the timber waste recycling to energy in Malaysia. The findings for the improvement factors from the current practices are authority enforcement, revenue from selling the timber waste, limitation of landfill spaces and public awareness. It is targeted that the research findings and recommendations will be useful for the waste authority, timber waste contractors and the public to reduce the timber waste being sent to landfill.